1994
DOI: 10.1101/gad.8.6.666
|View full text |Cite
|
Sign up to set email alerts
|

Differential disruption of genomic integrity and cell cycle regulation in normal human fibroblasts by the HPV oncoproteins.

Abstract: Genomic integrity is maintained by a network of cellular activities that assess the status of the genome at a given point in time, provide signals to proceed with or halt cell cycle progression, and provide for repair of damaged DNA. Mutations in any part of these pathways can have the ultimate effect of disturbing chromosomal integrity. Recent work suggests that p53 performs this integrator function in mammalian cells. Our present study demonstrates that in mortal cells, the expression of £6 and £7 viral onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
239
0
7

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(262 citation statements)
references
References 45 publications
(46 reference statements)
16
239
0
7
Order By: Relevance
“…Similar ®ndings were reported for human papilloma virus E7 protein (Vousden et al, 1993;Hickman et al, 1994;Demers et al, 1994;Szebos et al, 1994). On the other hand, adenovirus E1A protein was shown to convert REF52 cells to the permissive state only when mutant Ras protein was present at the same time (Perry et al, 1992) and papillomavirus E7 protein was found to induce aneuploidy in PALA treated normal human ®broblasts but due to massive cell death cell lines could only very rarely be selected (White et al, 1994). We do not have a de®nitive explanation for these di erences between the di erent viral proteins but it may be related to subtle di erences between the viral proteins in their capacity to dissociate E2F pocket protein complexes.…”
Section: Mrc5supporting
confidence: 79%
See 2 more Smart Citations
“…Similar ®ndings were reported for human papilloma virus E7 protein (Vousden et al, 1993;Hickman et al, 1994;Demers et al, 1994;Szebos et al, 1994). On the other hand, adenovirus E1A protein was shown to convert REF52 cells to the permissive state only when mutant Ras protein was present at the same time (Perry et al, 1992) and papillomavirus E7 protein was found to induce aneuploidy in PALA treated normal human ®broblasts but due to massive cell death cell lines could only very rarely be selected (White et al, 1994). We do not have a de®nitive explanation for these di erences between the di erent viral proteins but it may be related to subtle di erences between the viral proteins in their capacity to dissociate E2F pocket protein complexes.…”
Section: Mrc5supporting
confidence: 79%
“…Important among these is the CDK inhibitor protein p21. Mutation of p53 or interference with its activity, a condition generated by proteins coded by several DNA tumor viruses, makes cells permissive for DNA ampli®cation (Perry et al, 1992;White et al, 1994). DNA ampli®cation is seen as one indication for genome destabilisation which itself is a characteristic of immortalized and transformed cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next we determined the ability of the E7 proteins to trigger apoptosis. Analogously to other inducers of apoptosis, such as c-myc, Adenovirus E1A or E2F-1 (Evan et al, 1992;Hsieh et al, 1997;White et al, 1994), E7-induced apoptosis is more pronounced when the cells are deprived of serum survival factors . Therefore, NIH3T3 cells expressing the di erent E7 genes were cultured in medium containing 0.5% calf serum and the percentage of apoptotic cells was determined using time-lapse videomicroscopy.…”
Section: Resultsmentioning
confidence: 96%
“…As other stimulators of proliferation, the HPV16 E7 protein, besides the ability to deregulate the cell cycle, promotes apoptosis (Pan andGriep, 1994, 1995;White et al, 1994;Puthenveettil et al, 1996;Iglesias et al, 1998;Stoppler et al, 1998). Expression of HPV16 E7 in normal human ®broblasts (NHF) or in human keratinocytes results in a cytocidal response, which is much more evident in the absence of mitogenic signals and displays the typical features of apoptosis .…”
Section: Introductionmentioning
confidence: 99%